Properties of secondary discharge in plasma-liquid system based on rotating gliding discharge - Hamazin, D.K.; Iukhymenko, V.V.; Chernyak, V.Y.; Prysiazhna, O.V.; Martysh, E.V.; Bortyshevsky, V.A.; Korzh, R.V. (Вопросы атомной науки и техники, 2017)
This paper presents the results of secondary discharge based on rotating gliding discharge study in plasma-liquid system at atmospheric pressure. Discharge electrical parameters were investigated and geometrical parameters of the discharge channel were identified. In addition, the composition of the plasma and its temperatures (rotation and vibration temperatures) were determined. The discharge channel is broad and diffuse in the investigated range of parameters. This fact and the current-voltage characteristics indicate that this is a glow discharge. The large area of plasma-liquid interface allows efficient usage of such discharge for liquid processing for disinfection or pollutants destruction.